2008
DOI: 10.1002/eqe.803
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐dynamic test of a full‐scale CFT/BRB frame—Part II: Seismic performance of buckling‐restrained braces and connections

Abstract: SUMMARYThis paper is Part II of a two-part paper describing a full-scale 3-story 3-bay concrete-filled tube (CFT)/ buckling-restrained braced frame (BRBF) specimen tested using psuedo-dynamic testing procedures. The first paper described the specimen design, experiment, and simulation, whereas this paper focuses on the experimental responses of BRBs and BRB-to-gusset connections. This paper first evaluates the design of the gusset connections and the effects of the added edge stiffeners in improving the seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 3 publications
0
90
0
2
Order By: Relevance
“…Furthermore, several past studies have highlighted the risk of global BRB buckling induced by connection failure such as plastic hinges introduced at connection zone prior to core yielding ( Figure 1). For instance, Tsai et al [5] and Lin et al [6] reported the phenomenon of global buckling related to connection failure in BRB frame tests, and Wigle et al [7] discussed the effect of connections on BRB performance. Koetaka et al [8] discussed the conditions leading to instability, under which bending-moment transfer capacity at the restrainer ends is lost and gusset plates are designed to be rotationally rigid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several past studies have highlighted the risk of global BRB buckling induced by connection failure such as plastic hinges introduced at connection zone prior to core yielding ( Figure 1). For instance, Tsai et al [5] and Lin et al [6] reported the phenomenon of global buckling related to connection failure in BRB frame tests, and Wigle et al [7] discussed the effect of connections on BRB performance. Koetaka et al [8] discussed the conditions leading to instability, under which bending-moment transfer capacity at the restrainer ends is lost and gusset plates are designed to be rotationally rigid.…”
Section: Introductionmentioning
confidence: 99%
“…BEÇÇ'lerin eleman ve çerçeve benzeri sistem bazında davranışlarının yukarıda da görüldüğü gibi genel olarak kararlı olmasına karşın, BEÇÇ'lerin çerçeve içinde davranışlarında aynı Christopulos (2005) [26], [27]. Bu çalışmadaki çelik çerçeve, beton döşeme, çelik kiriş ve kompozit kolonlardan oluşmaktadır.…”
Section: Beçç'lerin çErçeve Sistemi Içerisindeki Deneyleriunclassified
“…Bu kritik boy kullanılarak, Denklem 7 BEÇÇ'nin basınç durumu için sağlanmalıdır. Denklem 7'deki etkili boy katsayısı ( ), [29] tarafından önerilen 0.65 olarak alınması durumunda hesaplanan değerler, deneyde kullanılan BEÇÇ'lerin eksenel basınç yüklerinden daha büyük olmasına rağmen [26] ve [27]'de bahsedilen burkulmalar meydana gelmiştir. Bu çalışma sonunda 0.65 olan etkili boy katsayısının bayrak levhasına ek plakalar eklenmesi ile kullanılabileceği, eğer ek plaka kullanılmazsa bu katsayının 2 olarak kullanılabileceği belirtilmiştir [27].…”
Section: Beçç'lerin çErçeve Sistemi Içerisindeki Deneyleriunclassified
“…However, the critical aspect of BRB performance requires inclusion of the connection effect in the assessment of the buckling failure mode. Takeuchi et al [1] summarized the most recent literature related to connection failure, which includes research highlights [2][3][4][5][6][7][8][9][10][11][12][13][14] and the steel structure seismic provisions [15,16]. Additionally, Lin et al [17] investigated the connection stress distribution by means of experimental testing and FEM analysis, proposing several design recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in Equation (11), the bending deformations of the connection zone become equal to rotational deformation of the end spring when ξ κ Rg = 3 [1]. The rotation angle of the lower and upper plastic hinges at the restrainer ends is expressed as follows:…”
Section: Introductionmentioning
confidence: 99%